Exploring a nature-related conflict from a capability perspective - Yuliana Griewald; Felix Rauschmayer (Helmholtz-Zentrum für Umweltforschung (UFZ), 2013)
Using the capability approach, we analyse a recent conflict around nature conservation in the city of Leipzig, Germany. Following its concept of flood protection, a state authority felled thousands of trees in a highly popular nature protection area, which culminated in public protests and lawsuits against the state authority. This analysis has a twofold aim: (1) to better understand the conflict at hand, and (2) to explore the advantages and limitations of using the capability approach for addressing such a nature-related conflict involving collective actors. Our analysis of the actors' positions and interplay between them goes along the lines of the capability approach and gives insight into the conflict from a freedoms perspective. We use qualitative research methods to examine the case, relying upon semi-structured interviews with key stakeholders as well as a document analysis. The capability approach offers a freedom-agency lens and proves to be helpful in analysing the conflict; however, to understand the case better, certain process-specific variables absent from a typical capability formation framework have to be considered as well. – – Wir benutzen den Capability- (Verwirklichungschancen-)Ansatz, um einen kürzlichen Naturschutzkonflikt in der Stadt Leipzig zu analysieren. Hier ließ eine staatliche Verwaltung im Rahmen ihres Konzepts von Hochwasserschutz Tausende Bäume in einem sehr beliebten Schutzgebiet fällen, was Proteste von Bürgern und Naturschutzverbänden auslöste. Unsere Analyse hat ein doppeltes Ziel: Wir wollen sowohl den Konflikt als auch die Vorzüge und Grenzen des Capability-Ansatzes besser verstehen, einen solchen naturbezogenen Konflikt mit kollektiven Akteuren anzugehen. Unsere Analyse der Akteurspositionen und -zusammenhänge vollziehen wir demzufolge an der Struktur des Capability-Ansatzes, was Einblick in den Konflikt aus einer freiheitsbetonenden Perspektive verschafft. Wir benutzen qualitative Forschungsmethoden um den Fall zu untersuchen, genauer gesagt: halbstrukturierte Interviews mit zentralen Stakeholdern wie auch eine Dokumentenanalyse. Der Capability-Ansatz bietet einen Blickwinkel, der Freiheit und menschliches Handeln in den Mittelpunkt stellt und sich als fruchtbar bei der Analyse des Konflikts erweist. Um alle wesentlichen Aspekte erfassen zu können, müssen jedoch weitere Variablen hinzugefügt werden, die typischerweise bei Capability-Analysen fehlen.
Keywords: 330